Resolving the Breakpoints of the 17q21.31 Microdeletion Syndrome with Next-Generation Sequencing - Itsara, Andy (Elsevier, 2012)
Recurrent deletions have been associated with numerous diseases and genomic disorders. Few, however, have been resolved at the molecular level because their breakpoints often occur in highly copy-number-polymorphic duplicated sequences. We present an approach that uses a combination of somatic cell hybrids, array comparative genomic hybridization, and the specificity of next-generation sequencing to determine breakpoints that occur within segmental duplications. Applying our technique to the 17q21.31 microdeletion syndrome, we used genome sequencing to determine copy-number-variant breakpoints in three deletion-bearing individuals with molecular resolution. For two cases, we observed breakpoints consistent with nonallelic homologous recombination involving only H2 chromosomal haplotypes, as expected. Molecular resolution revealed that the breakpoints occurred at different locations within a 145 kbp segment of >99% identity and disrupt KANSL1 (previously known as KANSL1). In the remaining case, we found that unequal crossover occurred interchromosomally between the H1 and H2 haplotypes and that this event was mediated by a homologous sequence that was once again missing from the human reference. Interestingly, the breakpoints mapped preferentially to gaps in the current reference genome assembly, which we resolved in this study. Our method provides a strategy for the identification of breakpoints within complex regions of the genome harboring high-identity and copy-number-polymorphic segmental duplication. The approach should become particularly useful as high-quality alternate reference sequences become available and genome sequencing of individuals' DNA becomes more routine.